Application the normalised difference vegetation index of landsat imagery to assess the desertification in Binh Thuan Province - Hien, Le Thi Thu (Vietnam Journal of Earth Sciences, 2014)
The vegetation is not cause of the desertification. but it is clearly reflected factor and is sensitive to effect of the desertification. this paper presents the criterias and finding of the desertification area in binh thuan by using landsat images through the normalised difference vegetation index (ndvi) and studies the relationships between ndvi with climateconditions. ndvi in a specific month in the long time for at least 20 years is a good indicator to define the desertification.the relationship between ndvi value below 0.1 and rainfall, moisture does not clearly describe the status of desertification. before 1979, the desertification area in binh thuan was only in phan thiet, tuy phong and bac binh districts with 42.6 km2, accounting for 0.5% of the total area, it located. But it has been spreaded during the period 1989-2003 with upto 1.193km2, accounting for 15% of the total area in 2003, and it is decreasing trend in period 2003-2010